Seismic Vulnerability Analysis of Prefabricated Concrete Frame with a Cam-Type Response Amplifying Device of Viscous Damper - Luyao Wei; Huijiao Nie (Advances in Civil Engineering)
A new type of limit response amplifying device (cam-type response amplifying device) was proposed in order to be able to solve the shortcomings of the seismic performance of the prefabricated concrete structures and the shortcomings of the existing response amplification devices that were prone to failure under rare earthquakes. On the basis of the unit library provided by ABAQUS, the secondary development was carried out and the dynamic time history analysis was performed on the solid model of the prefabricated frame structure. We selected the displacement angle between layers as the structural damage index and used the dynamic incremental method to analyze the seismic vulnerability of the uncontrolled structure without the cam-type response amplification device and the added damping structure. The results show that compared with the uncontrolled structure, the damping structure with a cam-type response amplification device had a significant reduction in the probability of reaching various failure states, and the seismic performance was effectively improved. The cam-type response amplifier had an excellent shock absorption effect under the action of all levels of the earthquake, which could effectively reduce the damage degree to the structure. Through the analysis of the vulnerability curve, it could provide the basis for the design method based on the behavior of the prefabricated concrete structures.